Study on fracture of coal samples with different fracture angles under microbial environment - Wen Wang; Yuxiang Song; Daping Xia; Xiaowei Lu; Songsong Guan; Chuanjiu Zhang; Yiwen Ju (PLoS ONE, 2025)
To investigate the permeability enhancement effect of microorganisms (Methanogens) on anthracite and their impact on coal strength, static fracture tests were conducted on semi-circular SCB specimens with prefabricated cracks of varying angles after immersion in neutral and microbial solutions. The fracture process was monitored using digital image correlation DIC and VIC-2D techniques. The effects of different solutions and prefabricated angle cracks on the strength, deformation characteristics and fracture toughness of anthracite were analyzed. Simultaneously, the influence of the displacement field at the prefabricated crack tip of the coal sample during the failure process and the evolution characteristics of the strain field of the coal sample at different stages of the process were analyzed. The test results show that the composite specimens with different slit angles and different solution environments have significant differences in the loading process. The samples mainly experience tensile failure, with shear failure as a supplement. Fracture toughness decreased as the angle between the crack and loading direction diminished. In the microbial-solution environment, the ability of the samples to resist crack propagation is further reduced. Tensile deformation initiation occurred at 57.97 ~ 86.7% P max for neutral solutions and 36.36 ~ 60.52% P max for microbial solutions. Microbial solutions induced earlier crack tip tensile deformation, promoting tensile failure and extending the fracture process zone (FPZ) length.